Overview of Usage Behavior of Personal Protective Equipment (PPE) Among Workers at PT. X in 2024 - Yuniyanti, Wahyu Siti; Millah, Izzatul (Budapest International Research and Critics University, 2025)
Occupational safety and health are the most important things. Based on Law Number 2 of 2017 concerning Construction Services, Article 52 states that service providers and sub-service providers in providing construction services must meet security, safety, health and sustainability standards. With occupational safety and health, workers can do all their work safely. The aim of this research is to describe the behavior of using Personal Protective Equipment (PPE) among workers at PT.X in 2024. The method used in this research is quantitative analytic with a cross sectional design study approach. The respondents of this study were 100 workers at PT. X. The results of this research show that of all the respondents observed, it was found that the majority of them complied with using PPE while carrying out their duties, namely 85.0%, 88.0%. 92.0% obediently wear a helmet when carrying out their duties, 92.0% obediently use safety shoes, 94.0% obediently use a helmet, 91.0% obediently use a mask, 93.0% obediently use goggles, and 93.0% obediently use gloves. Every employee must be educated to understand the benefits of using personal protective equipment when working and every employee must also be disciplined and consistent in using personal protective equipment while carrying out their duties at work.